High throughput rapid detection for SLM manufactured elements using ultrasonic measurement. (October 2019) - Liu, Yu; Li, Xiongbing; Chen, Chao; Song, Yongfeng; Ni, Peijun
Highlights: An ultrasonic high throughput method is developed for SLM manufactured elements. Both pore parameters and Young's modulus can be determined in a single experiment. The log-normal distribution is introduced to obtain quartiles of pore parameters. The results of other methods reveal the effectiveness of this work. Abstract: Both pore parameters and elastic properties are important for the elements manufactured by the Selective Laser Melting (SLM) technology; however, their measurements are usually destructive and time-consuming. Thus, the ultrasonic longitudinal and transverse wave velocities (dual-mode velocities) method is extended here; then it is combined with the longitudinal wave attenuation to develop an ultrasonic high throughput rapid detection for SLM manufactured elements. As the focal transducer is used, a multi-Gaussian beam model is introduced to correct the diffraction attenuation. Twenty-eight parameters can be obtained by a single ultrasonic experiment, including the pore parameters and their distributions, the two-point spatial correlation function, and the Young's modulus. Ti-6Al-4V samples with different porosities manufactured by SLM technology are used to conduct the ultrasonic experiment. The experimental results agree well with the results of metallographic, tensile experiment and micro-CT results. This method provides a useful tool for nondestructively, rapidly and accurately evaluating the pore parameters and elastic properties of SLM manufactured elements.